Phytopharmacognostic profiling of Prunus cerasoides Buch.-Ham. ex D. Don, heartwood - Kalyan Hazra; Deepak Kumar Achintya Mitra
Use of Prunus cerasoids Buch.-Ham. ex D. Don is mentioned in traditional texts as padmak with some of its medicinal values. Seeing the classical significance of the plant, the study was undertaken to develop a pharmacognostic and phytochemical blueprint of Prunus cerasoids heartwood. The primary goal of this study was to detect the bioactive flavonoids, like biochanin A, genistein and sakuranetin, in heartwood. Authenticated plant materials were subjected to pharmacognostical, physicochemical and HPTLC fingerprinting. Qualitative analysis in detecting phytocompounds in the extracts of varied solvent polarity was performed using LC-MS/MS orbitrap. The extraction efficiency was highest in polar organic solvent methanol, and LC-MS/MS ascertained the same. The significant outcome of this study was the extractability of the solvents in bringing down the active phytochemicals differently, and methanol was found to be the best-suited solvent. Maximum numbers and the major phytocompounds available were apigetrin, astilbin, betaine, biochanin a, caprolactum, catechin, choline, coumarin, eriodictyol, ethylmalonic acid, formononetin, genistein, glycitein, hematoxylin, naringenin, phloretin, pipecolic acid, prunin, quercetin, rutin, sakuranetin, taxifolin, and trifolin. The data set generated here had multi-faceted contributions, especially in phytopharmaceuticals. This multidimensional profile of the plant heartwood may serve as documentary evidence in preparing a genuine monograph.